AB0263 Trend in tuberculosis infection incidence in rheumatoid arthritis in spain: an observational cohort study (1999–2015) (trend-ar study). (12th June 2018) - Espinosa Malpartida, M.; Barbadillo, C.; Godoy, H.; Peña, M.; Macía, C.; García-Vadillo, A.; Morell, J.L.; Fernánde Prada, M.; Galindo, M.; Martínez-Prada, C.; Morado, C.; Herranz, Á.; et al.
Abstract : Background: There have been important changes in the management of rheumatoid arthritis (RA) in the last 20 years, due to the incorporation of new drugs. An increase in the incidence of tuberculosis infection (TB) has been observed because of reactivation of latent TB with the use of new treatments. Adequate prevention measures have been implemented. Objectives: To analyse the incidence and trend of hospital admissions for TB in patients with RA in Spain during the period between 1999 and 2015. Methods: This is a retrospective population based study. We analysed a national administrative database that includes a Minimum Basic Data Set (MBDS) of hospital admissions of patients with RA. Period: 1999 to 2015. The TB cases were identified by the presence in primary and secondary diagnosis of ICD 9 codes. The population at risk was estimated through the population census of the National Institute of Statistics, with an estimated prevalence of RA of 0.5%. The crude and adjusted rates of TB were calculated. The trend was analysed using Generalised Linear Models (GLM) using the year variable as the analysis variable. Results: Among all the admissions of patients with AR (338.343), 1209 (0.35%) were due to TB, 665 (55%) in women and 544 (44, 9%) in men. The mean age was 63.25 (SD 13.7). The mean of the Charlson index was 1.84 (SD 1.45), in women 1.63 (SD 1.3) and in men 2.09 (SD 1.59) (p<0.001). There were a total of 94 (7.8%) deaths during admission (6.9% in women, 8.8% in men, p=0.231). The TB age-adjusted rate during the study period was 42.78/100.000 inhabitants RA-year (28.2 in women and 100.74 in men). The TB age-adjusted rate in both sexes remains without significant changes between 1999 and 2015 (IRR 0.225; CI95% 0.985–1.025). During the period 1999–2011 an increase of the incidence is observed, while in the period 2011–2015 it is observed a decrease of the same (fig 1). Conclusions: Conclusion: In Spain, in patients with RA, the income rate in relation to tuberculosis increased from 1999 to 2010 and subsequently decreased in the period from 2011 to 2015. Disclosure of Interest: None declared